2024
DOI: 10.3390/prosthesis6010014
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Bleeding in Elderly Patients Undergoing Transcatheter Aortic Valve Implantation or Surgical Aortic Valve Replacement

Federica Jiritano,
Giuseppe Filiberto Serraino,
Sabato Sorrentino
et al.

Abstract: Background: Bleeding complications are strong predictors of mortality and major morbidity in elderly patients undergoing surgical aortic valve replacement (SAVR) or transcatheter aortic valve implantation (TAVI). Despite the high prevalence of frailty in this population, little is known about its effects on bleeding risk. Methods: We conducted a retrospective observational study of 502 patients undergoing isolated SAVR or TAVI between January 2015 and February 2022. The occurrence of blood products transfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
2
0
0
Order By: Relevance
“…A very recent report indicated that, even in octogenarian patients, a 5-year survival rate of over 60% could be reached for patients who left the hospital alive [9]. It also confirmed our early view that age in itself is not the only determinant of postoperative mortality [8]. Another of our older reports also indicated that the age and comorbidity of the referred patients increased in the period between 1987 and 2007 [10], until the introduction of TAVI.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…A very recent report indicated that, even in octogenarian patients, a 5-year survival rate of over 60% could be reached for patients who left the hospital alive [9]. It also confirmed our early view that age in itself is not the only determinant of postoperative mortality [8]. Another of our older reports also indicated that the age and comorbidity of the referred patients increased in the period between 1987 and 2007 [10], until the introduction of TAVI.…”
Section: Introductionsupporting
confidence: 80%
“…In one series, comparing SAVR and TAVI for two age groups, septuagenarians and octogenarians, the CEME device was used throughout for the SAVR, while the successive Sapien devices were used for the TAVI group. The investigated patients were very similar to the current group with respect to age, but coronary artery disease and the association of a CABG or any other procedure were seemingly absent [8]. A very recent report indicated that, even in octogenarian patients, a 5-year survival rate of over 60% could be reached for patients who left the hospital alive [9].…”
Section: Introductionsupporting
confidence: 59%